Principal Management Strategies for Improving Teacher Discipline in Junior High Schools: A Qualitative Study in South Aceh - Arifin, Syamsul; Ismail, Ismail; Bahrun, Bahrun; Fajri, Munawar; Kamaluddin, Kamaluddin (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
Teacher discipline remains a persistent challenge in many junior high schools and demands systematic management from school principals. This study explores principal management strategies for improving teacher discipline in public junior high schools in South Aceh Regency, Indonesia. Employing a descriptive qualitative case study design, data were collected through semi-structured interviews, field observations, and document analysis (e.g., attendance records, school regulations, and supervision notes). Participants were purposively selected to ensure information-rich perspectives and included two principals, six teachers, and two administrative staff from SMP Negeri 3 Trumon and SMP Negeri 4 Trumon Timur (N = 10). Data were analyzed thematically using an interactive process of data reduction, data display, and conclusion drawing, with trustworthiness strengthened through triangulation and member checking. The findings show that principals enact three interrelated strategies: (1) establishing and consistently enforcing clear disciplinary regulations (attendance, morning assembly, learning administration, and professional ethics); (2) applying a balanced reward–sanction system to reinforce compliance and responsibility; and (3) conducting continuous supervision through reminders, attendance monitoring, classroom observation, and periodic evaluation followed by coaching. These strategies were facilitated by effective communication, collaborative work culture, and supportive school policies, while limited resources and low teacher participation emerged as key constraints. Overall, integrated principal management contributes to a more orderly professional culture and supports improved school effectiveness in resource-constrained contexts.